Women and Infertility in a Pronatalist Culture: Mental Health in the Slums of Mumbai - Roberts L; Renati S; Solomon S; Montgomery S (Dove Medical Press, 2020)
Lisa Roberts,1 Solomon Renati,2 Shreeletha Solomon,3 Susanne Montgomery4 1School of Nursing, Loma Linda University, Loma Linda, CA 92350, USA; 2Department of Psychology, Veer Wajekar A. S. & C. College, Navi Mumbai 400702, India; 3Veer Wajekar A. S. & C. College, Navi Mumbai 400702, India; 4School of Behavioral Health, Behavioral Health Institute, Loma Linda University, Loma Linda, CA 92350, USACorrespondence: Lisa RobertsSchool of Nursing, Loma Linda University, 11262 Campus Street, Loma Linda, CA 92350, USATel +1 (909) 558-1000Fax +1 (909) 558-0719Email lroberts@llu.eduBackground: Infertility is a global problem, with high prevalence in India. As a pronatalist society, infertility is particularly problematic in India, causing stigma, shame, and blame especially for women. Infertility consequences for women include discrimination, social exclusion, and abandonment, putting them at high risk for mental health distress. Furthermore, mental health is highly stigmatized and specialized care is largely unavailable. Despite the cultural importance of childbearing, research on infertility distress and resulting mental health sequelae is lacking, particularly among low-income women. The purpose of this study is to assess mental health, using validated scales, among Mumbai slum-dwelling women with a history of infertility.Methods: We conducted a mixed-method, cross-sectional study. A focus group discussion with community health workers (n = 7) informed the development of a comprehensive survey. The survey consisted of validated scales whenever possible, in addition to questions pertaining to women’s sociodemographic and reproductive history. After rigorous forward and back translation, the surveys were conducted as face-to-face structured interviews due to low literacy levels and the research naiveté of our respondents. Interviews were conducted by culturally, linguistically, gender-matched, trained research assistants.Results: Mumbai slum-dwelling women of reproductive age suffering from infertility (N = 74) participated. Most (85%) women and their husbands (66%) reported previous infertility testing. Participants had elevated mental health distress (anxiety and depression symptomology) largely explained by general health, length of marriage, and coping strategy employed.Conclusion: Women facing the double stigma of mental health and infertility need innovative programs to address their challenges.Keywords: infertility, mental health, stigma, low-income women, Mumbai, India